Urban farming and its importance for environmental sustainability - Mohd. Hussain, Mohd. Ramzi; Yusoff, Norul Hafizah; Tukiman, Izawati (Institute of Research and Journals (IRAJ), 2017)
Urban farming is one of the approaches to achieve sustainable agriculture that is widely practiced by communities, especially around the rapid urbanization areas to address the environmental and economic issues like greenhouse effects and deprivation. Plenty efforts have been done over the past few decades in commercializing urban farming to the international, national and local level. The paper is aimed to discuss the literature framework of the growing demands of the urban farming activities within the city environment, and how it benefits the environmental sustainability concept. In addition, this paper describes the advantages of urban farming activities from the views of environmental, economical and social aspects which contribute very much to the urban sustainability. The benefits and potential of implementing urban farming within limited urban spaces are evaluated as it also may improve the quality of life among urban communities